Energy, the Exchange Rate, and the Economy : Macroeconomic Benefits of Canada's Oil Sands Production - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2006)
This paper describes potential benefits from Canada's expanding oil sands production, higher energy exports, and further improvements in the terms of trade. Contrary to the previous Canadian exchange rate literature, this paper finds that both energy and nonenergy commodity prices have an influence on the Canadian dollar, and some upward pressure on the exchange rate would therefore be expected. Model results suggest, however, that the impact on other tradable goods exports is limited.